Humour in the arts
1 online resource (244 pages)
Keywords: This collection demonstrates the usefulness of approaching texts—verbal, visual and aural—through a framework of humour. Contributors offer in-depth discussions of humour in the West within a wider cultural historical context to achieve a coherent, chronological sense of how humour proceeds from antiquity to modernity. Reading humorously reveals the complexity of certain aspects of texts that other reading approaches have so far failed to reveal. Humour in the Arts explores humour as a source of cultural formation that engages with ethical, political, and religious controversies whilst acquainting readers with a wide range of humorous structures and strategies used across Western cultures.